Práctica del cuidado espiritual en los entornos clínicos de salud (2024)
Spiritual care is a fundamental aspect within the competencies of professionals to attend to the spiritual needs of patients. It is important if you want to provide quality, compassionate and empathetic care to these and their families, with the aim of improving their spiritual well-being, reducing their suffering, improving their quality of life, and helping them make sense of their illness. Objective: Analyze the scientific literature on the practice of spiritual are in clinical health settings. Methodology: Scoping review of scientific literature. A search was carried out in the databases: PubMed Central, PubMed, ScienceDirect, Scielo, BVS. Research and review articles were included, published in English, Spanish and Portuguese, without time restrictions. Study without risk. Copyright is respected. Results: 33 articles were analyzed where both the practical application of spiritual care and the skills required to provide it were found. Conclusions: Spirituality is important to find meaning in suffering and a way to integrate it into health environments is through the practice of spiritual care and the development of professional and human skills for its application.